Clinical characteristics of apixaban prescription in AF patients with single dose-reduction criterion: the ASPIRE (efficAcy and safety of aPixaban in rEal-world practice in Korean frail patients with atrial fibrillation) study - Choi, JungMin; Lee, So-Ryoung; Kwon, Soonil; Ahn, Hyo-Jeong; Lee, Kyung-Yeon; Park, Jong-Sung; Choi, Jong-Il; Lee, Sung Ho; Heo, Jung Ho; Oh, Il-Young; On, Young Keun; Yu, Hee Tae; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Data on off-label reduced dose risk among patients with atrial fibrillation (AF) who qualify for a single-dose reduction of apixaban is scarce. Objectives: We prospectively assessed apixaban dosing and clinical characteristics in AF patients meeting a dose reduction criterion. Methods: The multicentre, prospective cohort study, the efficAcy and Safety of aPixaban In REal-world practice in Korean frail patients with AF (ASPIRE), encompasses patients with AF who met the criteria for a single-dose reduction of apixaban and were given varying doses of apixaban, either the on-label standard dose or the off-label reduced dose. Results Of 2000 patients (mean age 74.3±7.9 years, 55.8% women), 29.7% were ≥80 years, 62.6% weighed ≤60 kg, and 7.8% had serum creatinine ≥1.5 mg/dL. Of these, 51.3% were prescribed an off-label reduced dose of apixaban. The off-label group was characterized with older age, more comorbidities, and antiplatelet agents, while the on-label group had more prior strokes. Physicians preferred off-label reduced dose in the 'marginal zone,' defined as age 75–80 years, weight 60–65 kg, and creatinine levels 1.2–1.5 mg/dL. Conclusions: In real-world clinical setting of the Korean population, off-label reduced dose apixaban was administered to nearly half of the patients who qualified for a single dose reduction. This reduced dosage was more commonly prescribed to patients with frail characteristics, while patients with a history of stroke were more often given the standard dose as per the label. A future study is planned to contrast the safety and effectiveness of the standard dose against the reduced dose of apixaban in this population.